Unlocking Copper from Electronic Waste: Optimized Leaching Strategies and Rapid Analytical Chemistry Evaluation - Olomu, Efe [UNESP]; Ferreira, Dennis Silva; Edenir, Rodrigues Pereira-Filho; Pereira, Fabiola [UNESP] (Eurowaste SRL, 2025)
This study presents a novel method for evaluating copper (Cu) extraction efficiency by combining chemometric approaches with non-invasive analytical techniques, including energy-dispersive x-ray fluorescence (ED-XRF) and laser-induced breakdown spectroscopy (LIBS). Aligned with Process Intensification (PI) principles, our methodology utilizes the Design of Experiments (DoE) approach to streamline decision-making in metal recovery processes. While the in-situ generation of Cu ions in the liquid medium yielded suboptimal results, this approach warrants further investigation to optimize its potential. On the other hand, our findings demonstrate that LIBS and XRF are highly effective in differentiating leachates based on Cu signals, offering advantages such as higher analytical frequency and lower operational costs compared to traditional methods like Inductively Coupled Plasma Optical Emission Spectroscopy (ICP OES). These noninvasive techniques enhance process understanding and enable more efficient and informed decision-making. By integrating PI with DoE, this study advances Cu recycling strategies from Waste Electrical and Electronic Equipment (WEEE), paving the way for more sustainable and cost-effective recovery processes. This approach holds significant promise for addressing the growing challenges of e-waste management and resource recovery.